Process quality control troubleshooting and interpretation of data - Ott, Ellis R. 1906- (ASQ Quality Press, 2005)
Ellis Ott taught generations of quality practitioners to be explorers of the truth through the collection and graphical portrayal of data. from a simple plea to plot the data to devising a graphical analytical tool called the analysis of means (ANOM), Ott demonstrated that process knowledge is to be gained by seeking the information contained within the data. In this newest version of Ott's classic text, the authors have strived to continue down the path that he created for others to follow. Additions to this revised edition include: the use of dot plots as an alternative to histograms; digidot plots; adding events to charts; emphasis on the role that acceptance control charts play in controlling risks and the computation of average run length (ARL); a new chapter devoted to process capability, process performance, and process improvement, including the use of confidence intervals for process capability metrics; narrow-limit gauging as another means of assessing the capability of a process; Six Sigma methodology; design resolution; scatter plot matrices as applied to datasets of higher dimensions; and a new chapter on measurement studies.
Keywords: Process control -- Statistical methods.; Quality control -- Statistical methods.; elektronické knihy; electronic books